PEMBUATAN WEBSITE JEKS TOURISM SEBAGAI MEDIA INFORMASI AGROWISATA JERUK KEPROK DI KABUPATEN KEPULAUAN SELAYAR - Ilham Ahmad; Andryanto A; Adilham Adilham; Karma Karma (Jurnal Abdimas Bina Bangsa, 2023)
The Regency of Kepulauan Selayar holds significant potential in orange agrotourism, but the available information is still limited. Therefore, the implementation of this community service aims to create a website named "JeKS Tourism" as a medium for providing information on orange agrotourism in the Regency of Kepulauan Selayar, accessible through the website https://jekselayarisland-tourism.com/. This website offers information about natural, cultural, and artificial tourist attractions such as orange picking activities. Additionally, it provides information about processed orange products such as orange juice, dodol, and preserves. The website development method involves active participation from the local farming community and the regional government, especially the Department of Tourism. The output of this project results in a website containing informative content, including text, images, and maps. Through the implementation of this initiative, it is expected that Orange Agrotourism in the Regency of Kepulauan Selayar can become well-known and attract tourists, thereby enhancing the income and welfare of the local community